Effect of the varied load conditions on the tribological performance and the thermal characteristics of PEEK-based hybrid composites. (September 2016) - Lin, Leyu; Schlarb, Alois K.
Abstract: The friction and wear behavior of PEEK and a multi-scale particle filled PEEK was characterized by using a velocity increasing approach during one sliding wear test without changing of polymer specimen and counterbody. The results derived demonstrated that the incorporation of various fillers remarkably improved the tribological performance of PEEK, especially under severer load conditions, e.g. under a pv-condition of 4 MPa and 0.5–4 m/s, the mean specific wear rate reduced from 19 mm 3  N −1  m −1 to 0.42 mm 3  N −1  m −1 after incorporation of rigid fillers, and similarly, the lowest friction coefficient was obtained from PEEK composite, which is about 0.1. In addition, similar friction coefficients and wear rates of PEEK and PEEK composite are gained from velocity increasing tests compared to those evaluated from constant velocity tests, which means that the successful application of the velocity increasing technique in the investigation of the tribological performance of polymer materials can obviously reduce the time and material expenses. Finally, based on the observations of the worn surface, in addition to the rolling effect of the particles between body and counterbody and the alleviation of stress concentration on the SCFs due to improvement of the matrix stiffness by incorporating rigid particles, an additional protective effect of particles on the SCFs was observed. The particles accumulate in front of the fibers, which reduces the direct contact between the counterbody and SCF, and therefore, the debonding and removals of fibers were alleviated. Highlights: The addition of fillers significantly improved the friction and wear properties. The load varying test was successfully applied. A novel protective effect of particles on the SCFs was observed.